Crystal Structure of the 2′‐Specific and Double‐Stranded RNA‐Activated Interferon‐Induced Antiviral Protein 2′‐5′‐Oligoadenylate Synthetase - Hartmann, R. (Scand J Immunol, 2008)
2′‐5′‐oligoadenylate synthetases are interferon‐induced, double‐stranded RNA‐activated antiviral enzymes which are the only proteins known to catalyse 2′‐specific nucleotidyl transfer. This first crystal structure of a 2′‐5′‐oligoadenylate synthetase reveals a structural conservation with the 3′‐specific poly(A) polymerase that, coupled with structure‐guided mutagenesis, supports a conserved catalytic mechanism for the 2′‐ and 3′‐specific nucleotidyl transferases. Comparison with structures of other superfamily members indicates that the donor substrates are bound by conserved active site features while the acceptor substrates are oriented by nonconserved regions. The 2′‐5′‐oligoadenylate synthetases are activated by viral double‐stranded RNA in infected cells and initiate a cellular response by synthesizing 2′‐5′‐oligoadenylates, that in turn activate RNase L. This crystal structure suggests that activation involves a domain–domain shift and identifies a putative dsRNA activation site that is probed by mutagenesis. We demonstrated that this site is required both for the binding of dsRNA and for the subsequent activation of OAS. This RNA‐binding site is different from known RNA‐binding site; rather than forming a defined three‐dimensional domain, it is located at the interface of the two major domains in OAS. This novel architecture ensures that the dsRNA helix can make simultaneously contact with both domains of OAS and ensure the subsequent structural rearrangement leading to the activation of OAS. Our work provides structural insight into cellular recognition of double‐stranded RNA of viral origin and identifies a novel RNA‐binding motif.